Notions About the National Traditions of the People of the Oasis and the Valley - Jumakhanov Shavkatdjon; Jalolidinova Muxtasarxon; Zoirjanov Shakhbozbek (Zien Journals, 2022)
This article examines the importance of geographical factors in ethno-processes such as the emergence of ethnos, people, nation, self-expression on the world stage, longevity over the centuries and the historical formation of the people, the understanding of ethnocultural identity. In particular, within the essence of the concept of "ethnos" the geographical factors that led to the formation of the culture of the Uzbek ethnos and its cultural traditions, values, style of dress, the uniqueness of national cuisine are analyzed. The main results of the article were a comparison and analysis of the degree of influence of the regional factor on the formation of the national culture of the population of the oasis and valley areas. The main focus was on the style of dress of the population of the regions, the type and consumption of national dishes, national ceremonies, performance styles of dances and other features.
Keywords: Ethnogenesis; ethnography; valley; oasis